Mesoporous Nitrogen-Doped Carbon for the Electrocatalytic Synthesis of Hydrogen Peroxide - Fellinger, Tim-Patrick; Hasché, Frédéric; Strasser, Peter; Antonietti, Markus (Journal of the American Chemical Society, 2012)
Mesoporous nitrogen-doped carbon derived from the ionic liquid N-butyl-3-methylpyridinium dicyanamide is a highly active, cheap, and selective metal-free catalyst for the electrochemical synthesis of hydrogen peroxide that has the potential for use in a safe, sustainable, and cheap flow-reactor-based method for H2O2 production.